The preparation of activated carbon from South African coal for use in PGM extraction - Kruger, Diederick Johannes (North-West University, 2007)
Activated carbons used in the Platinum Group Metals extraction industry are characterised by large internal surface areas and a great affinity for platinum, palladium and ruthenium. It is therefore necessary in this study to develop a method to produce an activated carbon that is suitable and yet cost effective, for use in the extraction of PGM's. The quality of the coal-based activated carbon may not prove to be as good as activated carbon produced from other traditional sources, but the production costs involved may make South African coal a feasible alternative feedstock. The purpose of this research is to prepare activated carbon from a South African based bituminous coal by physical activation. The activated carbon produced are characterised by BET surface area, activated carbon pH and phenol adsorption studies. The results of the different characterisation methods for the prepared activated carbons are compared to the results of a commercially available activated carbon, Norit RO 0.8 (control sample). Bituminous coals from various sources including Witbank Seam 4 and New Vaal are used. The preparation method chosen is raw material activation by means of physical activation with superheated steam. The effects of process variables such as activation time (1-3 hr) and temperature (600 - 800°C) are studied in order to optimise those preparation parameters. Activated carbon surface area is characterized by means of nitrogen adsorption isotherms at 77K. BET surface area analysis showed that Witbank Seam 4 coal activated at a temperature of 800°C and activation time of 3 hours, resulted in a surface area of 340m2/g. Quality control of each sample was performed by measuring the pH of a known amount of the prepared activated carbon in distilled water over time. Results showed that the pH of some of the prepared activated carbons reached a value of 11. Phenol adsorption results for the different activated carbons prepared corresponded well to the results obtained for the Norit RO 0.8 activated carbon sample.
Thesis (M. Ing. (Chemical Engineering))--North-West University, Potchefstroom Campus, 2008.
Keywords: South Africa; Activated carbon; PGM